Constitution 74th amendment act and the provision of infrastructure services an insight into some deficiencies - Rahmatullah, S.M. (2011)
Adequate provision of urban infrastructure is a prerequisite for overall economic growth and sustainable development. But it is very unfortunate that a gap has emerged between what is needed and what exists with regard to infrastructure in urban India. The haves as against the have nots have been relatively suffering more because of the non-availability of the requisite infrastructure in urban areas. The Constitution 74th Amendment Act has been enacted to strengthen the urban local bodies (ULBs) to ensure, among other things, adequate provision of infrastructure in urban India. But, there is lack of clarity in the Amendment Act about the functional responsibilities and financial powers of ULBs and involvement of NGOs in urban governance for the development and provision of adequate infrastructure in urban areas. The Second Administrative Reforms Commission has also pointed out the inadequacies of the Amendment Act. An attempt has been made in this article to define infrastructure and deal with its classification and significance, list out the features of the Amendment Act and highlight its deficiences that affect the effective development and provision of infrastructure facilities. The intention here is to examine the issue with a view to continue the discourse on the Amendment Act so as to pave the way for further reforms to strengthen the system of development and provision of infrastructure services in urban Indi a by taking into consideration the requirements of all the people including the common man. - Reproduced.
Keywords: Urban development - India; India.Constitution - Amendments - 74th; Urban development